2021
DOI: 10.3390/ani11071878
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Supplementing Broiler Diets with Biological Curcumin, Zinc Nanoparticles and Bacillus licheniformis on Growth, Carcass Traits, Blood Indices, Meat Quality and Cecal Microbial Load

Abstract: The current study aimed to investigate the influence of dietary zinc nanoparticles (ZnNPs), curcumin nanoparticles (CurNPs), and Bacillus licheniformis (Bl) on the growth, carcass, blood metabolites, and the count of some cecal microorganisms of Indian River (IR) broilers. Chicks were allotted into seven experimental groups: control group, 1st, 2nd and 3rd groups were given diets enriched with ZnNPs, CurNPs and Bl (3.0, 5.0 and 2.0 cm3/kg diet, respectively). The 4th, 5th and 6th groups were given diets supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 91 publications
5
67
3
Order By: Relevance
“…In comparison with ducks in ochratoxin A (2 mg/kg −1 ), dietary curcumin increased the growth performance of ducks fed corn contaminated with ochratoxin A [ 20 ]. Abd El-Hack et al (2021) reported that biological curcumin can improve the growth performance of broilers increasing nutrient intake and antioxidant capacity [ 21 ]. In addition, similar studies demonstrated that supplementing the diet with curcumin enhanced growth performance by increasing antioxidation capacity and improving the intestinal integrity of poultry, such as in Arbor Acres broiler chickens [ 22 ], Ross broiler chickens [ 12 ], wenchang broiler chickens [ 8 ], and quail [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with ducks in ochratoxin A (2 mg/kg −1 ), dietary curcumin increased the growth performance of ducks fed corn contaminated with ochratoxin A [ 20 ]. Abd El-Hack et al (2021) reported that biological curcumin can improve the growth performance of broilers increasing nutrient intake and antioxidant capacity [ 21 ]. In addition, similar studies demonstrated that supplementing the diet with curcumin enhanced growth performance by increasing antioxidation capacity and improving the intestinal integrity of poultry, such as in Arbor Acres broiler chickens [ 22 ], Ross broiler chickens [ 12 ], wenchang broiler chickens [ 8 ], and quail [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peptides and essential oils also act as a powerful antimicrobial agent against Gram negative and/or Gram positive bacteria ( El-Saadony et al, 2020 , 2021b , c ; Saad et al, 2020 , 2021c ; El-Tarabily et al, 2021 ). The antimicrobial mechanism of these compounds is represented in their electrostatic interaction with specific compounds in the bacterial cell wall, which disrupted and allowed the additives' entry and changes the behavior of DNA in the bacterial cell causing cell death ( Abd El-Hack et al, 2021b , c , d ).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Meissner's plexuses which sense the lumen environment might be related to smooth muscle hypertrophy ( Pavone et al., 2019 ). Through this study, we recommend paying attention to pigeon breeding and public awareness to reduce the risk of contracting diseases and transmitting these diseases to other avian and animal species as well as humans, through the application of biosecurity & quarantine measures, strengthening the general health of pigeons by using of balanced feed and supplying the bird with safe environmentally friend preparations as herbal extracts ( Abou-Kassem et al., 2021a ; Abd El-Hack et al., 2021a ), essential oils ( Alagawany et al., 2021a ; Dosoky et al., 2021 ; El-Tarabily et al., 2021 ; Mohamed et al., 2021 ), essential amino acids ( Abou-Kassem et al., 2021b ), bioactive peptides ( El-Saadony et al., 2021a , b ), probiotics ( Alagawany et al., 2021b , El-Saadony et al., 2021c ), prebiotics ( Abd El-Hack et al., 2020 , 2021b ; Yaqoob et al., 2021 ), plant-derived natural bioactive compounds ( El-Saadony et al., 2021d ; Raza et al., 2021 ; Seidavi et al., 2021a , b ), biological synthesized nanoparticles ( Abd El‐Hack et al., 2021c , d ; El-Saadony et al., 2021e ), and phytogenic compounds ( Abo Ghanima et al., 2021 , Ashour et al., 2021a ; Abdel-Moneim et al. ; Ashour et al., 2020b , Reda et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%